The prevalence of sexual activity, and sexual dysfunction and behaviours in postmenopausal woman in Poland - Czajkowska, Kamila B.; Lew-Starowicz, Zbigniew; Szymańska, Monika (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction: Despite the aging of the population, there is limited data available about sexual life and behaviours among of postmenopausal and late postmenopausal women. Aim of the study was to assess the prevalence of sexual dysfunction, behaviours, and preferences in the Polish population in 2015. Material and methods: This observational survey study involved 538 women, of whom 220 were over 50 years old. The main focus was on the differences and changes between older age groups, mainly 50-59 years and over 60 years. Results : For 80.9% of the women above 50 years old, sex played at least a moderately important role in life. Sex was definitely important and very important for 40.45% of them. Most women over 50 years old (65.5%) were sexually active. Regardless of age, the respondents were more likely to have sexual intercourse several times a month. Less than half of the women over 50 years old (42.7%) realised their sexual fantasies. Women in the group of 50-59 years old statistically less often than younger women declared that the frequency of intercourse they had was too small. There was a statistical tendency showing that women up to 49 years old declared more sexual problems than older women. Women over 50 years old reported fewer problems in comparison to younger women, e.g. less often they claimed that sex is not pleasurable (p = 0.064). Conclusions : The prevalence of sexual activity declines with age, yet a substantial number of woman engage in vaginal intercourse, oral sex, and masturbation even past the seventh decade of life.